1999
DOI: 10.1093/intimm/11.9.1541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cmv1 candidates by genetic mapping and in vivo antibody depletion of NK cell subsets

Abstract: The mouse chromosome 6 locus Cmv1 controls resistance to infection with murine cytomegalovirus (MCMV). We have previously shown that Cmv1 is tightly linked to members of the NK gene complex (NKC) including the Ly49 gene family. To assess the candidacy of individual NKC members for the resistance locus, first we followed the co-segregation of Cd94, Nkg2d, and the well-characterized Ly49a, Ly49c and Ly49g genes with respect to Cmv1 in pre-existing panels of intraspecific backcross mice. Gene order and intergene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Altogether the results suggested that self-licensed NK cells, possibly regulated by background genetic effects, contribute to highly efficient detection and elimination of viral targets. However, several reports have shown that Ly49G 2 + NK cells in B6 mice rapidly expanded in response to proliferation cues (36) or exposure to one of several different viruses (3739). Moreover, licensed Ly49C/I+ NK cells were since shown to diminish viral control in MCMV-infected B6 mice (40).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether the results suggested that self-licensed NK cells, possibly regulated by background genetic effects, contribute to highly efficient detection and elimination of viral targets. However, several reports have shown that Ly49G 2 + NK cells in B6 mice rapidly expanded in response to proliferation cues (36) or exposure to one of several different viruses (3739). Moreover, licensed Ly49C/I+ NK cells were since shown to diminish viral control in MCMV-infected B6 mice (40).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were infected with 2 * 10 6  PFU of Δm157 MCMV for 5 days. Viral titers of the stock virus or mouse organs (spleen and liver) were evaluated in vitro by standard plaque assays on a confluent BALB/c mouse embryonal fibroblast monolayer, as previously described40.…”
Section: Methodsmentioning
confidence: 99%
“…Segregation analysis of polymorphic markers, including microsatellite markers, gene sequences and anonymous probes, with respect to Cmv1 lead to the localization of Cmv1 to a 0.35-cM interval in two independent genetic maps. [110][111][112] The map generated by our group revealed gene order and intergene distances (in cM) in the vicinity of Cmv1 as: (Figure 2a). A high-resolution physical map of the Cmv1 genetic interval based on long-range restriction mapping by PFGE and the assembly of a contig of YAC and BAC clones translated the genetic interval into 1.6 Mb of genomic DNA containing a minimum of 18 transcription units including the 14 Ly49 gene cluster (Figure 2b, c).…”
Section: Cloning Of Cmv1mentioning
confidence: 99%
“…112 These results excluded Nk1.1, Cd94 and Nkg2d, while retaining the Ly49 gene cluster as candidates for Cmv1. [110][111][112] Interestingly, a similar mapping approach being performed by a second group initially excluded Ly49 genes as potential candidates by placing Cmv1 distal to Ly49b gene, raising the possibility that one or more NKC genes could be involved in the resistance/susceptibility phenotype. 115 Sequence comparison between Cmv1 r and Cmv1 s strains indicated allelic differences for transcripts analyzed in the Cmv1 interval 116,117 (Figure 2b, Figure 3), precluding assessment of their candidacy based upon mutation analysis.…”
Section: Cloning Of Cmv1mentioning
confidence: 99%
See 1 more Smart Citation